Terapia de fotobiomodulação nas tendinopatias: revisão sistemática - Salani, Renata (2017)
Tendinopathy is a term that refers to several damages in the tendo and that consequently generates an inflammatory response. Photobiomodulation therapy is able to reduce the inflammatory process and increase collagen synthesis, thereby decreasing painful sensation and decreasing the chance of rupture. Method: Search of the literature in PubMed between 2010 and 2016, only randomized clinical trials in the English language and that presented at least one control group. The evaluation of the studies was performed by the PEDro scale. Results: Nine studies were included in this study and eight showed efficacy of the photobiomodulation therapy in tendinopathies, but the lack of the necessary parameters in these studies for better applicability of the results is observed. Conclusion: Phototherapy is effective in the treatment of tendinopathies, but for future studies it is necessary a better methodological quality of the studies, as well as the full citation of all the parameters used.